Urinary dysfunction in children is associated with exposure to environmental tobacco smoke - Schneider, Dona; Colaco, Marc; Markowski, Paul; Barone, Joseph G. (Journal of pediatric urology, 2013)
Environmental tobacco smoke (ETS) is known to cause significant morbidity across a wide variety of organ systems. The purpose of this study was to examine the relationship of ETS exposure with pediatric urinary dysfunction. Participants were drawn from a university-based pediatric urology practice throughout the first half of 2011. All patients who presented with a chief complaint of urinary dysfunction were approached to participate (N = 184). Exclusion criteria eliminated all but 71 subjects. Of these, 68 subjects and their parents completed age-appropriate questionnaires on ETS exposure and symptom severity. Data were analyzed using descriptive statistics and relationship between exposure and outcome was evaluated via Spearman correlation analysis. A total of 68 children with no known etiology for their urinary dysfunction were evaluated for symptom severity and ETS exposure. Participants demonstrated a significant positive correlation (rho = 0.592 for those 4–10 years; rho = 0.415 for those 11–17 years) between ETS exposure and severity of their urinary symptoms. These data indicate a positive relationship between ETS exposure and urinary dysfunction among children with no other obvious etiology for their symptoms. Physicians should inform parents of the potential dangers of childhood ETS exposure, including the possible relationship with urinary dysfunction.